'And they lived happily ever after': Community music and higher education?. Issue 2 (8th July 2011) - Coffman, Don
This article argues that community music and higher education have sufficient shared visions to overcome past philosophical differences. Each party brings valuable contributions in what some speculate is only a 'marriage of convenience'.